How to develop reading comprehension strategies in a foreign language - Chirinos Napanga, Yanett Daysi (2019)
• Beyond the traditional view of reading as a passive skill, it is clear that reading comprehension is definitely an interactive psycholinguistic process, and should be seen as treated as such by teachers and students. • Ausubel´s proverbial claim that "the student knows" seems to be grounded on solid empirical experience. It seems to be a fact that each person has a whole body of prior knowledge and past experiences they hold in their brains and bring to the class should not be ignored. • As a student's reading skills to develop, comprehension is vital. There necessitates a deliberate, deliberate interaction between the text, the reader, and the context. • Prior knowledge is not activated automatically: we need to activate it the means by means of strategies. Strategies, then, play a central role to foster comprehension and in the long run, learning. • So as the students have different learning styles, along with differences types of intelligences, there are now a variety of strategies that may be used to foster reading comprehension. • The sociocultural context of the student (as stored in his/her background knowledge) greatly influences reading comprehension. Relating the reading topics presented in class to the students´ context does facilitate comprehension and makes them feel more secure, thus fostering learning. • We can generate background knowledge departing from the particular to the general, that is, progressively until the student has built a conceptual readiness of his/her own.